Strategies for the Role of Parents and Teachers in Motivating Student Learning - Fitri, Yulia; Latif, Latif (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
The purpose of this study was to determine the strategy of the role of parents and teachers in motivating student learning. The author raised this title because there are several students in class IV SDN 010 Barngan who still have low learning motivation. This can be seen from the lack of concentration of students to pay attention to the teacher during learning activities. The type of research used is research with a qualitative descriptive approach. The data collected from interviews with parents and teachers, observation and documentation. This research uses data collection techniques, data reduction, data presentation, and data verification/conclusion drawing. The results showed that there are 3 strategies carried out by parents in motivating student learning, namely giving praise, giving gifts and punishment. Meanwhile, there are 3 teacher strategies carried out, namely using appropriate learning methods, as a motivator and good classroom manager.